Age and petrogenetic constraints on the lower glassy ignimbrite of the Mount Somers Volcanic Group, New Zealand. Issue 3 (3rd July 2017) - van der Meer, Q. H. A.; Waight, T. E.; Whitehouse, M. J.; Andersen, T.
ABSTRACT: The Mount Somers Volcanic Group (MSVG) forms a large (c. 18, 000 km 2 ) calc-alkaline volcanic complex on New Zealand's Eastern Province. U–Pb secondary ion mass spectrometry (SIMS) spot ages on zircon from the lower glassy ignimbrite in Rakaia Gorge reveal a bimodal distribution of 99.0 ± 0.5 and 96.3 ± 0.5 Ma (2σ). These ages are within error of previous (unpublished) zircon sensitive high resolution ion microprobe ages but have a precision that enables identification of two distinct episodes of zircon crystallisation, indicating magmatic activity over a period of at least 2.5 Ma. The younger age is interpreted to represent the emplacement age of the ignimbrite. The older age may originate from the assimilation of underlying ignimbrites or prolonged magma chamber processes. Combined O and Hf isotopes in zircon indicate that melt compositions for the c. 99 and c. 96 Ma magmatic episodes were very similar and intermediate between the local upper crust and mantle-derived melts, supporting formation through hybridisation of mantle and crustal-derived melts. MSVG magmatism preceded, coexisted with and was succeeded by local mafic alkaline HIMU-type magmatism (97.0 ± 0.5 Ma and younger) on the nearby Pahau Terrane. By contrast, the mafic component of the MSVG was derived from a depleted and potentially subduction-modified source associated with the Rakaia Terrane.